Outcome Predictors in Patient with Traumatic Intracerebral Hemorrhage in Hasan Sadikin General Hospital Bandung - Tara M Mulyawan; M Zafrullah Arifin; Firman P Tjahjono (Journal of Medicine and Health, 2019)
Predictions about patient outcomes can help doctors make decisions. Intracerebral hemorrhage acccompanied by brain injury can increase mortality but specific studies on outcomes of patients with traumatic intracerebral hemorrhage are still rare. The purpose of this study was to determine the factors that influence the outcome of traumatic intracerebral hemorrhage patients in the RSHS period from January to December 2017. This is an observational study with cross sectional method, categorical comparative analytic. The study involved 60 traumatic intracerebral hemorrhages aged ? 15 years who were hospitalized in RSHS. The data was analyzed univariately and bivariately using Chi Square statistical test, Eta correlation test and contingency coefficient. The results showed age (p = 0.003), GCS scores assessed at admission (p <0.001), and the presence or absence of other brain hemorrhages (p = 0.050) significantly affected the patient's outcome. Gender (p = 0.932), mechanism of injury (p = 0.739), and pupillary response (p = 0.056) did not affect the outcome significantly. In conclusion, the factors that influence the outcome of traumatic intracerebral hemorrhage patients are age, GCS score, and presence or absence of other brain hemorrhages. Keywords: intracerebral hemorrhage, trauma, predictors, outcome